The Pineal Hypothesis for Drug Dependence - Francesco Crespi (International Physiology Journal, 2018)
The pineal gland constitutes a major neuroendocrine organ in the brain. By mean of its neurohormone melatonin it transduces exogenous signals such as circadian and seasonal variations of light and temperature into proper hormonal changes which adjust and adapt internal endocrine functions. Alteration of circadian rhythms has been associated with affective disorders, psychosomatic diseases and cancer. It has been observed that light deprivation, which stimulates (the enzymes responsible for) melatonin production in the pineal, enhances the animal's ethanol preference. Similarly, administration of the pineal hormone to rats maintained under normal conditions of constant photoperiod also induced ethanol drinking. Our hypothesis is that in normal conditions melatonin might be acting as a cerebral
Keywords: neurohormone